Determinants of firms' inputs sourcing choices: The role of institutional and regulatory factors - Mattia Di Ubaldo; Iulia Siedschlag (The Economic and Social Research Institute (ESRI), 2018)
Using the theoretical framework of global sourcing with firm heterogeneity, we examine determinants of inputs sourcing choices of manufacturing firms established in the EU countries. To this purpose, we combine information on the ownership structure and company accounts from the Orbis data set with input-output data from the World Input-Output Tables (WIOT) and with information on institutional and regulatory factors at country level provided by international organisations. Our research findings indicate that manufacturing firms that source inputs intra-firm via foreign direct investment (FDI) across EU countries are larger, more productive, more intensive in tangible and intangible capital and less intensive in skills than manufacturing firms that source inputs at arm's length. The probability of integrating inputs by manufacturing firms across EU countries is positively linked with the strength of legal systems, flexibility of labour markets and negatively linked to corporate tax rates and financial development in host countries. Less efficient insolvency procedures are associated with a higher probability of sourcing inputs intra-firm via FDI relative to arm's length sourcing. The probability of sourcing inputs via FDI is negatively linked to sectoral restrictions to FDI and positively linked to the impact of service regulations on downstream industries.
Keywords: F12; F15; F23; F68; 330; Global sourcing; input-output linkages; structural policy